The reality of specialized academic accreditation at Tishreen University from the point of view of postgraduate students (A field study at the Faculty of Arts and humanities) Dr. Osama Mohammad - محمد, أسامة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The study problem centered on the following: What is the reality of specialized academic accreditation at Tishreen University from the point of view of graduate students? The study also aimed at studying the reality of specialized academic accreditation, determining the reality of the curricula used for postgraduate students, explaining the reality of training and scientific production for postgraduate students, in addition to determining the reality of academic programs and how to evaluate them, and clarifying the reality of the faculty members at the university. The descriptive analytical approach was followed. The study also reached a set of results, the most important of which are the following: The existence of great difficulties at Tishreen University to obtain partial specialized academic accreditation related to the five previous mentioned variables. A complete absence of the student training process at Tishreen University from the point of view of graduate students in the College of Arts, and a marked decrease in the scientific production process in the College of Arts at Tishreen University, and the lack of financial capacity for students to publish abroad, with the absence of funding by the university administration for the process of publishing external research And the low standard of the academic curricula available in the College of Arts, its lack of modernity and its need for major changes and modernization in its old traditional content.